Gelatin‐Immobilized High Aspect Ratio Gold Nanocrystals: An Efficient Catalyst for 4‐Nitrophenol Reduction. Issue 3 (1st October 2015) - Sharma, Shyamalima; Bora, Pritom J; Boruah, Monalisha; Dolui, Swapan K
ABSTRACT: This article highlights the progress in the synthesis of gelatin‐immobilized anisotropic gold (Au) nanoparticles and their catalytic activity in 4‐nitrophenol (4‐NP) reduction. The catalytic process is monitored by using the UV–visible spectrophotometer, and the effect of shape and aspect ratio on the Au nanoparticles on catalytic activity is investigated. The catalytic process follows a pseudo–first‐order kinetics with the rate constant in the range of 1.1 × 10 −3 s −1 to 4.5 × 10 −3 s −1 . It is found that high aspect ratio Au/gelatin shows the best conversion (99.89%), which is comparable to the spherical seed (99.93%). After a certain catalytic reaction, the recovery of expensive catalysts and their reuse without losing their activity is an essential element in the sustainable process development. The immobilization of the catalyst into gelatin allows the high aspect ratio Au/gelatin nanocatalyst to be recovered and reused for a number of cycles.